Sports and child development - Christina Felfe; Michael Lechner; Andreas Steinmayr (Institute for the Study of Labor (IZA), 2011)
Despite the relevance of cognitive and non-cognitive skills for professional success, their formation is not yet fully understood. This study fills part of this gap by analyzing the effect of sports club participation, one of the most popular extra-curricular activities, on children's skill development. Our results indicate positive effects: both cognitive skills, measured by school performance, and overall non-cognitive skills improve by 0.13 standard deviations. The results are robust when using alternative datasets as well as alternative estimation and identification strategies. The effects can be partially explained by increased physical activities replacing passive leisure activities.
urn:nbn:de:101:1-201111213467
Keywords: J24; J13; I12; 330; skill formation; non-cognitive skills; physical activity; semi-parametric estimation; Kinder; Bildungsniveau; Kognition; Sport; Deutschland